2006
DOI: 10.1124/jpet.106.105213
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Metabolite Profiling Reveals CYP1A2-Mediated Metabolism of NSC686288 (Aminoflavone)

Abstract: NSC686288 [aminoflavone (AF)], a candidate chemotherapeutic agent, possesses a unique antiproliferative profile against tumor cells. Metabolic bioactivation of AF by drug-metabolizing enzymes, especially CYP1A monooxygenases, has been implicated as an underlying mechanism for its selective cytotoxicity in several cell culture-based studies. However, in vivo metabolism of AF has not been investigated in detail. In this study, the structural identities of 13 AF metabolites (12 of which are novel) in mouse urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…Previous reports indicate that CYP1A2 metabolizes AF into a number of different species that have been characterized including a hydroxylated metabolite. 11 A recent study suggests that flavonoid small molecules with hydroxylation in the 3 position have a greater propensity to demonstrate prooxidant characteristics than those lacking this substitution. 40 We postulate that CYP1A2 promotes the metabolism of AF to a 3-hydroxylated derivative which may contribute to the prooxidant characteristics of AF as modeled in Figure 5d.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports indicate that CYP1A2 metabolizes AF into a number of different species that have been characterized including a hydroxylated metabolite. 11 A recent study suggests that flavonoid small molecules with hydroxylation in the 3 position have a greater propensity to demonstrate prooxidant characteristics than those lacking this substitution. 40 We postulate that CYP1A2 promotes the metabolism of AF to a 3-hydroxylated derivative which may contribute to the prooxidant characteristics of AF as modeled in Figure 5d.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies have characterized and identified covalent drug adducts which indicates that AF metabolite(s) alkylate DNA. 8,11 Though AF may alkylate DNA, it likely possesses a mechanism of anticancer activity distinct from most alkylating agents also known to induce DPC formation. Studies are underway to identify the proteins involved in DPC formation following AF treatment which could shed additional light into its unique mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen aminoflavone metabolites appear prominently in the loadings plot as the ions that greatly contribute to the separation of aminoflavone treatment from vehicle treatment in the first PC ( Fig. 2C; Chen et al, 2006).…”
Section: Identification Of Metabolites Through Metabolomic Comparisonmentioning
confidence: 99%
“…Pooled human liver microsomes were purchased from Puracyp (Carlsbad, CA). Mice and rat liver microsomes were prepared from male C57BL/6 mice and male CD rats, respectively (Chen et al, 2006). The microsomal protein concentration was determined by bicinchoninic acid protein assay.…”
Section: Methodsmentioning
confidence: 99%